Hydrothermal processing, as an alternative for upgrading agriculture residues and marine biomass according to the biorefinery concept : a review - Ruiz, Héctor A. (2013)
The concept of a biorefinery that integrates processes and technologies for biomass conversion demands efficient utilization of all components. Hydrothermal processing is a potential clean technology to convert raw materials such as lignocellulosic materials and aquatic biomass into bioenergy and high added-value chemicals. In this technology, water at high temperatures and pressures is applied for hydrolysis, extraction and structural modification of materials. This review is focused on providing an updated overview on the fundamentals, modelling, separation and applications of the main components of lignocellulosic materials and conversion of aquatic biomass (macro- and micro- algae) into value-added products.